A Prospective Observational Study on Use of Acute Physiology and Chronic Health Evaluation-II and Sequential Organ Failure Assessment Score to Predict Outcome - Keyal, Niraj Kumar; Jha, Sudhakar; Parween, Shahnaj; Haque, Ishfa Banu; Ansari, Tauqueer; Ansari, Istiyaque (Journal of Nepal Health Research Council, 2025)
Background: Acute physiology and chronic health evaluation –II (APACHE-II) and Sequential organ failure assessment (SOFA) is used to predict overall mortality and sepsis outcome in the intensive care unit (ICU) respectively. There are limited studies that have shown that both score can be used to predict mortality in surgical and medical patients admitted in the intensive care unit.Methods: It was a prospective, observational study in a level three intensive care unit of National Medical College, Birgunj. This study was conducted in 542 patients admitted in the mixed intensive care unit of medical; college. Demographic data was gathered from each patient in the preformed sheet at the time of presentation to the intensive care unit. Outcome of patients was recorded in terms of mortality, discharge toward and leave against medical advice. The descriptive data are presented as the number and percentage for categorical data and mean ± standard deviation for continuous data according to their distributionResults: Five hundred forty two patients were included in this study. 340(62.7%) were males and 202(37.3%) were females. 440(81%) patients survived and went home, 65(12%) expired, 26(5%) left the hospital against medical advice (LAMA) and 11(2%) gave do not resuscitate orders (DNR). The discrimination power was similar for APACHE II and SOFA scores (AUC=0.732 versus 0.771, respectively, p>0.05). APACHE II score>8.5 and SOFA >3.5 was cut off to predict mortality.Conclusions: SOFA and APACHE II has similar discriminating power to predict mortality in all group of patients in a mixed intensive care unit.Keywords: APACHE II; intensive care units; SOFA.